STRES KERJA INSTRUKTUR (Survei Terhadap Para Instruktur Pada Unit Training Centre PT. Bank ABC. Tbk, Jakarta 2005) - willy Arafah (Universitas Trisakti, 2005)
The purpose of this research is to find out the relationship between job stress instructors who are working in training center unit of PT. Bank ABC.Tbk with the types of personality, personal role's conflict and interest in education. The dependent variable of this study is job stress and independent variables are the types of personality, personal role's conflict and interest in education. This study was conducted in training centre unit of who are working in the unit of PT. Bank ABC.Tbk. They are holders of Tbk by carrying out a survey of 30 (thirty) instructors 30 educational disciplines who were selected randomly. Time period of this study was from Februedial correlation and i degrees from undergraduate studies (Strata-1) of various to March 2005 and data analyzed through simple regression multiple regressions. The research findings are as follows: (1). there is a positive correlation between tynoe correlation between personal role's conflict and job stress. (2). there is a positive Correlation between personal roles conflict and job stress, (3). but there is no significant correlation between interest in education and job stress. Furthermore, (4). there is positive correlation between types of personality and personal role's conflict towards job stress. in conclusion of this research that job stress instructors who are working in training center unit of PT. Bank ABC.Tbk can be affected by the types of personality and personal role's conflict.